An observational study of nasal cavity toxicity in cancer patients treated with bevacizumab. (November 2014) - D'Amico, Mauro; Pagano, Mauro; Pasa, Ambra; Puntoni, Matteo; Clavarezza, Matteo; Gennari, Alessandra; Gozza, Alberto; Zanardi, Silvia; Defferrari, Carlotta; Provinciali, Nicoletta; Campazzi, Eleonora; Campora, Sara; et al.
Abstract : Background: The nasal cavity is a vulnerable zone which may be damaged by vascular disorders. We systematically assessed the frequency and severity of nasal cavity alterations during bevacizumab treatment, to determine its clinical relevance and factors contributing to its onset. Patients and methods: We conducted a hospital-based cohort study in 47 consecutive patients with advanced cancers who were on treatment with chemotherapy and bevacizumab at different doses. All patients underwent otolaryngology (ENT) examination at the time of study initiation. Results: The mean number of cycles at first ENT examination was 16 (standard deviation = 14). A total of 45 patients (96%) showed nose mucosal lesions, of whom 30% had erosions and 62% had grade 1 – 2 epistaxis. One patient had septal perforation. Grades 1 – 4 sinus disorders were noted in 60%. There was a significant trend to a higher risk of grade ≥ 2 nasal events for bevacizumab doses > 7.5 mg/kg, concomitant taxane use and digital nasal self-manipulation. Conclusions: We found a high incidence of nasal cavity lesions in patients receiving bevacizumab, with evidence for a dose-related effect. Most cases were low grade and manageable without drug interruption, but severe toxicity may rarely occur. Oncologists should be aware of this unusual event.